1993
DOI: 10.1213/00000539-199305000-00026
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Ketorolac on Postoperative Analgesia and Ventilatory Function After Laparoscopic Cholecystectomy

Abstract: Ketorolac, a nonsteroidal anti-inflammatory drug, is alleged to produce postoperative analgesia without opioid-related side effects. Patients undergoing laparoscopic cholecystectomy were assigned randomly to receive either ketorolac or a placebo (saline) according to a double-blind protocol. Preoperative (baseline) pulmonary function was evaluated using a Respiradyne II monitor. Patients received midazolam, 2 mg, and 2 mL of either ketorolac, 60 mg (n = 31), or saline (n = 29), 20-40 min before surgery. Anesth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
24
0

Year Published

1996
1996
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(26 citation statements)
references
References 0 publications
2
24
0
Order By: Relevance
“…In a study conducted by Ure et al, the most intensive pain was in the right upper quadrant and port entry sites in the first 24 hours following the procedure. [23] The pain type in this study is in accordance with the observations made by Ure et al Additionally, the preemptive efficacy of NSAIDs [16] and tramadol [24] is well known and have been used in this study. The fact that four patients were "painful" and two patients were "very painful" in Group T has been linked to the length of surgery and extent of tissue trauma caused by surgery.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…In a study conducted by Ure et al, the most intensive pain was in the right upper quadrant and port entry sites in the first 24 hours following the procedure. [23] The pain type in this study is in accordance with the observations made by Ure et al Additionally, the preemptive efficacy of NSAIDs [16] and tramadol [24] is well known and have been used in this study. The fact that four patients were "painful" and two patients were "very painful" in Group T has been linked to the length of surgery and extent of tissue trauma caused by surgery.…”
Section: Discussionsupporting
confidence: 85%
“…The total opioid consumption was calculated by multiplying the number of deliveries at the end of the 24th hour by the number of boluses (one bolus is 3 ml and ter laparoscopic cholecystectomy. [15,16] However, it has been shown that their combination with opioids provide more effective pain control [17] and reduces opioid consumption and associated side effects as the results of a study by Iohom et al, which was conducted on 30 total hip arthroplasty patients and 25 mg dexketoprofen was used transdermally 24 hours before and 48 hours after the surgery suggests. [18] Similarly, in this study, addition of dexketoprofen trometamol to tramadol has significantly decreased VAS scores in the postoperative period which is the primary endpoint.…”
Section: Discussionmentioning
confidence: 99%
“…[12][13][14][15][16]19 Reduction of PG synthesis would be expected to diminish nociceptor sensitization and inflammatory responses that normally accompany movement and stretching of injured tissues. [25][26][27] The CoX selectivity of FA remains unclear, although it was Data are mean ± SD. *P < 0.0001 vs baseline values.…”
Section: Discussionmentioning
confidence: 99%
“…Recently adopted surgical methods using the laparoscopic technique to approach the abdomen [4, 5]entail substantially less severe impairment in the functional integrity of the abdominal wall, thus causing less pain [6, 7, 8]and allowing better patient mobility, which is of utmost importance for the prevention of respiratory complications [9, 10]. …”
Section: Introductionmentioning
confidence: 99%